Meningkatnya Penjualan UMKM Kabupaten Tuban : Dipengaruhi oleh Promosi, Harga, dan Kemampuan Beradaptasi dengan Teknologi Pemasaran : Studi pada UMKM yang Mendaftar di Aplikasi Grabfood - Yahyaningtyas, Errina Eka; Rusdi Hidayat Nugroho (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Promotion carried out online is one of the effective marketing activities. Online promotions are currently growing rapidly in Indonesia, business people are starting to carry out online promotions by connecting with online marketing applications. One of the online applications currently being developed in Indonesia is the Grab application. Price is one component that can influence the sales of a product. The price of a product is seen from the quality of the product itself. By adapting to using online marketing applications, you can build and improve your business and maintain the reputation of your digital business. Increasing sales is what business people want. MSME business actors in Tuban Regency realize the importance of innovating new marketing strategies using digital-based technology which is increasingly being used effectively to expand market share. This research uses a quantitative approach. The sample in this study was the entire population, namely 141 respondents. The research method used was distributing questionnaires. Data analysis techniques using multiple linear regression analysis include analysis of validity, reliability, normality, multicollinearity, heteroscedasticity, R2 determination test, F test and T test, using SPSS 26 to process the data. These results show t-values ​​of 2.721 for promotion (<t-table 1.977), 2.632 for price (<t-table 1.977), 6.013 for adaptability to marketing technology (<t-table 1.977). ). All with significance less than 0.05. Therefore, Promotion, Price, Ability to Adapt to Marketing Technology have a significant positive effect on increasing sales. The F test produces an F value of 99.131 (>f-table 2.671) with a significance of 0.000 <0.05. Therefore simultaneously Promotion, Price, and Ability to Adapt to Marketing Technology have a significant effect on increasing sales. The conclusion of this research is that the independent variables promotion, price, adaptability of marketing technology partially have a significant positive effect on the dependent variable of increasing sales. Simultaneously promotion, price, and the ability to adapt to marketing technology have a significant effect on increasing sales.